Unraveling the Genetic Heartbeat: Decoding Cardiac Involvement in Duchenne Muscular Dystrophy - Valeria Novelli; Francesco Canonico; Renzo Laborante; Martina Manzoni; Alessandra Arcudi; Giulio Pompilio; Eugenio Mercuri; Giuseppe Patti; Domenico D’Amario (Biomedicines)
Cardiomyopathy represents the most important life-limiting condition of Duchenne muscular dystrophy (DMD) patients after the age of 20. Genetic alterations in the DMD gene result in the absence of functional dystrophin protein, leading to skeletal/cardiac muscle impairment. The DMD incidence is one in 5000 live male births. Identifying the genetic background, in addition to DMD disease-causing variants, is one of the unmet needs in understanding the cardiac disease’s pathogenetic mechanisms and its prognostic implications. The clinical scenario is made even more intricate by the difficulty in predicting the onset and progression of cardiomyopathy, as no clear genotype/phenotype correspondence has been found thus far. The evaluation of genes involved in the onset of primary cardiomyopathies could explore the hypothesis that changes in cytoskeletal and sarcomeric protein function are the modulators of ventricular dysfunction in DMD patients. In the last decade, with the advent of next-generation sequencing (NGS) technology, many disease-causing genes and modifiers have been identified. Assessing the genetic origin of the phenotypic variability of the disease in both the onset and progression of cardiomyopathy in DMD would be extremely helpful in managing these patients. This review article aims to spotlight the genetic background associated with Cardiomyopathy in DMD patients toward a more predictive personalized model of care.